An Overview of Scenario Approaches: A Guide for Urban Design and Planning - Abou Jaoude, Grace; Mumm, Olaf; Carlow, Vanessa Miriam (Journal of planning literature, 2022)
Rising complexities and uncertainties have emphasized the need to employ scenario thinking in urban design and planning. While different scenario methods have been widely used across disciplines, a comprehensive review of scenario approaches in planning literature is limited. Thus, we provide an overview of scenarios and existing scenario approaches currently in practice. We also review a scenario building process to provide a guide for developing scenarios in the context of urban design and planning. The process highlights the different steps that contribute to adaptive planning and improve decision-making.